Users’ Guide for the African Standard and Guidelines for Quality Assurance in Higher Education (ASG-QA) - HAQAA Initiative (HAQAA Initiative, 2020)
The African Standards and Guidelines for Quality Assurance in Higher Education (ASG-QA) were developed in 2018 as part of the Pan-African Quality Assurance and Accreditation Framework (PAQAF), which provides a continental framework to harmonise higher education quality assurance systems and promote compatible methodologies, endorsed by the African Union. The ASG-QA were developed following a mapping of existing standards at national and regional levels, a comparison with other existing international standards and guidelines as well as a broad stakeholder consultation. This was done with the support of the HAQAA Initiative – Harmonisation, Accreditation and Quality Assurance in African Higher Education, funded by the European Union in support of its partnership with the African Union. The aim of this Users’ Guide is to further support the implementation of the ASG-QA by providing practical guidance and explanation, including:
clarifications to improve the understanding and interpretation of the ASG-QA, particularly related to aspects of individual standards that have proved challenging in the first years of their use;
guidance on the implementation of the standards for HEIs and QAAs in the early stages of development;
examples of how HEIs and QAAs can demonstrate that they are meeting the commitments of the ASG-QA when undergoing internal or external reviews.
Keywords: Quality Assurance; Higher Education